Propuesta Metodológica Para El Cálculo A Gran Escala De Árboles Individuales Mediante El Uso De Datos Lidar (Airborne Light Scanner, Als) (2021)
In this study, a methodological alternative was presented for the detection of individual trees through the use of LIDAR point clouds, where the step by step for the calculation of the trees and extraction of the information in shapefile format through the use MicroStation Connect, Terrasolid version 19, Inertial Explorer 8.7, Spatial Explorer was described. Quality control was carried out on the methodology presented using three random areas in which the manual identification of the trees was performed, identifying the sub-segmentation and the over-segmentation, which were compared under a confusion matrix to measure the precision in the performance of the methodology, the information used for this study was taken in China, in the island province Hainan an area of 7.8ha and supplied by the company Ewart aerospace inc, which used a Riegl VUX LR sensor of 820 KHz with an LN200 IMU on a DJI M600- UAV platform